Analysis of the Use of Non-Cash Payment Instruments in Realizing A Less Cash Society in the Environment - Hasanah, Nur; Jenita, Jenita (Husnayain Business Review, 2023)
The purpose of this study is to determine the partial and simultaneous influence between promotional attractiveness, product knowledge, benefit perception and income level with the use of non-cash payment instruments, and also to determine the effect of using non-cash payment instruments in realizing a less cash society. The population is all lecturers in PTKIN and PTKIS Riau Province totaling 954 with samples calculated based on the formula of Issac & Michael resulting in a sample of 211 respondents. The sampling method uses Cluster Proportional Random Methode. And the data is analyzed with Analysis Path. The results showed that partially or simultaneously the variables of promotional attractiveness (X1), product knowledge (X2), benefit perception (X3), and income level (X4) had a positive and significant effect on the use of non-cash payment instruments (Y) with the contribution of independent variables to the dependent variable of 73.37%, and the remaining 26.63% influenced by other variables. While the variable use of non-cash payment instruments (Y) has a positive and significant effect on the variable less cash society, with a contribution value of 47.61% while the remaining 52.4% is influenced by other factors outside this study.